Consumer attitudes to food quality products : Emphasis on Southern Europe - Kuipers, Abele; Hocquette, Jean-Francois; Klopcic, Marija (EAAP - European Federation of Animal Science, 2013)
Quality foods, such as traditional, EU certified, organic and health claimed are part of a growing trend towards added value in the agri-food sector. In these foods, elements of production, processing, marketing, agro-tourism and speciality stores are combined. Paramount above all is the link to the consumer, which requires a personal approach. At this point, one enters the field of food consumer science. This can be seen as a hybrid of two distinct sciences. On one hand, there is the 'hardware' component, i.e. the science of food. On the other hand, the 'software' component, related to the science of consumers' preferences and behaviour. In animal science, nearly all attention is given to the 'hardware' aspect. However, to build a successful business in quality food products, the 'software' aspect is essential. This publication devotes special attention to the consumer and gives insight into an area of knowledge still very much in development. It is intended to enhance understanding of the complex relationships in the route from products to consumers and offers practical solutions in this field. This publication includes review articles covering basic aspects of food consumer science and research trends in the field, and a series of country reports and articles on relevant studies related to the topic, with emphasis on Southern Europe.